(untitled) (Journal of Business and Technology (Dhaka), 2016)
Procrastination and its impacts on students of various academic levels have been scrutinized for many years, but how the students involved in procrastination are utilizing their hours of a day have not been answered yet. To find out the answer, this study randomly sampled 1000 undergraduate private university students in Bangladesh and found that occasional procrastinators use most of their time for the academic purposes than non academic purposes if were judged against chronic and severe procrastinators. Moreover, it identified that, the academic results of the undergraduate students were negatively associated with their intensity of procrastination. Moreover, the amount of time they used for academic purpose was inversely inclined to their frequency of procrastination. On the contrary, this study also found that, the amount of time used by undergraduate students for non-academic purposes was positively associated with their extent procrastination. Journal of Business and Technology (Dhaka) Vol.10(2) 2015; 37-56